“Classes always go from here to there”: continuities and transformations in the spaces designed for primary schools in Rio Grande do Sul, Brazil (1883-1928) - de Freitas Ermel, Tatiane (Historia y Memoria de la Educación, 2020)
The state of Rio Grande do Sul/Brazil, following the international guidelines and models related to implementation, dissemination and improvements of primary education, undertook, between the end of the 19th century and the first decades of the 20th century, initiatives that responded to the need for the construction of school facilities. The objective of this paper is to analyze the ideas and actions that marked the continuities and the transformations related to government intervention in school spaces. For this purpose we will use a model of a school building, from 1883; a standard design project, from 1899; a model of an agricultural school, from 1919; and a competition for school constructions, from 1928. The documentary research, of a historiographical character, uses as primary sources the reports by the Direction of Public Instruction and Public Works of the State of Rio Grande do Sul. The paper shows the permanence throughout these decades of certain aspects, especially those concerning the need for tax revenue to pay for the building of schools, their location in the cities and villages, hygienist issues, the teachers' places of residence, and the graded school system. Among the main transformations, we highlight the design of cornerless, adaptable rooms; mixed classes; rooms for different activities, such as museums, laboratories, administrative rooms, libraries, and spaces for school movie theaters and radio stations. These new state prescriptions were partially aligned with the New School principles, which were introduced in Brazil especially throughout the decade of 1920; in keeping with this movement, it was thought that the design of school spaces should consider the central role that children would play in the educational process, taking into account their needs and curiosities.